Macroeconomics - O$1 (BSullivan, Arthur.s; Sheffrin, Steven M.; Perez, Stephen J.; O$1 (BSullivan, Arthur. s (Upper Saddle River, NJ : Pearson, 2009)
Students come into their first Economics course thinking they will gain a better understanding of the economy around them. Unfortunately, they often leave with many unanswered questions. To ensure students actively internalize economics, O'Sullivan/Sheffrin/Perez use chapter-opening questions to spark interest on important economic concepts, applications that vividly illustrate those concepts, and chapter-ending tools that test and solidify understanding.
Introduction : what is economics? -- Key principles of economics -- Exchange and markets -- Demand, supply, and market equilibrium -- Measuring a nation?s production and income -- Unemployment and inflation -- The economy at full employment -- Why do economies grow? -- AD/AS -- Fiscal policy -- The income expenditure model -- Investment and financial markets -- Money and the banking system -- The federal reserve and monetary policy -- Modern macroeconomics : from the short run to the long run -- The dynamics of inflation and unemployment -- Macroeconomic policy debates -- International trade and public policy -- The world of international finance.
1
Keywords: Macroeconomics